To solve the equation \(3n + 9 + 4n = 2\), we can follow these steps:
Step 1: Combine like terms on the left side of the equation.
\[3n + 4n + 9 = 2\]
This simplifies to:
\[7n + 9 = 2\]
Step 2: Subtract 9 from both sides of the equation to isolate the term with \(n\).
\[7n + 9 - 9 = 2 - 9\]
This simplifies to:
\[7n = -7\]
Step 3: Divide both sides by 7 to solve for \(n\).
\[\frac{7n}{7} = \frac{-7}{7}\]
This simplifies to:
\[n = -1\]
Putting it together:
- Step 1: Combine like terms to get \(7n + 9 = 2\).
- Step 2: Subtract 9 to get \(7n = -7\).
- Step 3: Divide by 7 to get \(n = -1\).